Microstructural engineering through high enthalpy states: implications for far-from-equilibrium processing of structural alloys - Mishra, Rajiv S.; Gupta, Sanya (Frontiers in Metals and Alloys, 2023)
Metallic materials derive their strength and ductility from their microstructural features. The general principle of alloying is not only to control the phases present in the alloys, but also how the alloying elements can help in microstructural control during the processing of materials. The overall thermodynamic framework of using free energy to explain the stability of an alloy has two significant terms, enthalpy, and entropy. Engineering alloys are processed by several far-from-equilibrium processes. During the processing, the materials are in metastable states. The metastability can also be purposely enhanced through alloy design. This paper provides a perspective on how “high enthalpy states” can be used to tailor the microstructure to overcome the conventional strength-ductility tradeoff. The emergence of new manufacturing processes also provides unique opportunities to design alloys to maximize the potential of such processes. A few illustrative examples are presented to tie the historical use of high enthalpy states and point to future opportunities. Co-development of advanced materials for disruptive new manufacturing processes can be enhanced through integrated computational materials engineering approaches.